THE USE OF ARTIFICIAL INTELLIGENCE IN MEDICAL PROBLEM SOLVING: A REVIEW OF CURRENT APPLICATIONS AND FUTURE PROSPECTS - Mirjahan Istamov (Journal of new century innovations, 2023)
Abstract: The use of artificial intelligence (AI) has become increasingly prevalent in the field of medicine in recent years. AI technologies have been applied to various medical problems, including diagnosis, prognosis, and treatment planning. This paper provides an overview of the current applications of AI in medical problem- solving, with a particular focus on machine learning (ML) techniques. The paper also discusses the benefits and limitations of AI in medical problem-solving and identifies areas for further research.